PENGARUH PEMBERIAN UMPAN YANG BERBEDA TERHADAP HASIL TANGKAPAN IKAN PADA ALAT TANGKAP BUBU BAMBU DI PERAIRAN SUNGAI BATANG MERSIP KABUPATEN SAROLANGUN - Dedek Saputra; Yurleni; Yoppie Wulanda (Jurnal Riset Multidisiplin Edukasi, 2025)
The Batang Mersip River is a river that has potential in capture fisheries, one of which is in Mersip Village, Limun District. Fishing activities in the Batang Mersip River operated by fishermen include bamboo traps. This study aims to analyze the effect of different baits on fish catches in bamboo traps in the Batang Mersip River. This study used an experimental fishing method. This study consisted of 3 treatments based on the type of bait used with 30 bamboo units, each bait consisting of 10 bamboo traps with a bait weight of 50 grams per trap with 10 repetitions. This study was conducted for 10 days. Each treatment was given a distance of 10 meters. The results of this study showed that different types of bait had a significant effect (P <0.05) on the number (tails) and weight (grams) of fish. The highest number of catches was in the cricket bait treatment of 102 fish and the lowest catch was in the treatment without bait of 16 fish. Meanwhile, the highest catch weight was obtained with cricket bait, weighing 4850 grams, while the lowest was obtained with the unbaited treatment, weighing 311 grams. This study concluded that the effect of providing cricket bait in bamboo traps yielded better results than worm bait and unbaited fish.